2016
DOI: 10.12816/0031515
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of Halal Supply Chain Management from the Perspective of Malaysian Halal Food Manufacturers

Abstract: The purpose of this paper is to unveil critical success factors which are important for Halal Supply Chain Management from the perspective of Malaysian Halal Food Manufacturers. Societal Marketing concept prevailing in organizations and Halal Supply Chain Management is the practical shape by delivering value and societal value chain in complete supply chain, taking care of consumers and society's long term interests simultaneously meeting company's requirements. For this study 389 questionnaires were sent to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Indeed, respondents stated the need for information related to raw material production and technology that can drive the halal supply chain. However, it is important to note that the supply chain issues did not emerge from the interviews with such strong a focus as in many recent studies (Ali et al , 2017; Nor et al , 2016; Soon et al , 2017; Talib et al , 2015a; Tieman et al , 2012). The supply chain challenges connect market and institutional contexts and may be due to the fragmented set of producers along the food chain and to missing institutions within the halal governance system.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, respondents stated the need for information related to raw material production and technology that can drive the halal supply chain. However, it is important to note that the supply chain issues did not emerge from the interviews with such strong a focus as in many recent studies (Ali et al , 2017; Nor et al , 2016; Soon et al , 2017; Talib et al , 2015a; Tieman et al , 2012). The supply chain challenges connect market and institutional contexts and may be due to the fragmented set of producers along the food chain and to missing institutions within the halal governance system.…”
Section: Resultsmentioning
confidence: 96%
“…Maka dari itu pelatihan terhadap karyawan mengenai penerapan kebijakan dan prosedur halal harus dilakukan. Selain menjaga komitmen UMKM halal dalam menerapkan kebijakan halal, pelatihan dapat meningkatkan keahlian karyawan (Din & Daud, 2014;Khan et al, 2018;Nor et al, 2016;Talib et al, 2014). Karyawan yang terlatih akan memiliki tingkat produktivitas yang lebih baik daripada karyawan yang tidak menerima pelatihan.…”
Section: Supply Chain Resourcesunclassified
“…Malaysia UAE, Bahrain, Saudi Arabia, Pakistan, Oman, Kuwait, Qatar, Jordan and Indonesia are Islamic countries in halal industry and listed according to their rank of market size (Rachman & Syamsuddin 2019). World halal food industry is now sprouting especially is Asia, where countries have taken an initiative of traceability system & improvement of halal standards (Nor et al, 2016). Once halal is taken as a choice of lifestyle then for halal the range of options increases exponentially (Razak et al 2015).…”
Section: R M B Rmentioning
confidence: 99%
“…Yusuf et al (2016) expressed that halal industry recently has attracted global interest, from Muslim as well as non-Muslim countries and impact of halal products affects both of them. Nor et al (2016) quoting some studies asserted that United Nations reported that after Christianity, Islam is the second largest religion with a recorded annual growth of 6.4 percent while Christianity has annual growth of 1.46 percent currently Muslims in the world are 1.62 billion representing 23.4 percent of world anticipated population of 6.9 billion for 2010 & halal food market worth 16 percent of total world food industry, and in future estimated to be 20 percent of global food products. Asia has 63 percent, Africa 24 percent and Europe 10 percent of global market.…”
Section: R M B Rmentioning
confidence: 99%
See 1 more Smart Citation